The impact of culture on transformation processes - Vineet Kumar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Culture has a dominant role in social change due to its influence on the principles, opinions, activities, and systems of society. Therefore, the work explores various aspects of culture in influencing and adapting change processes. This paper will study the impacts of cultural motion on the change of individual and group identity, the effect of promoting imaginative thinking and innovation, and the mediating effect of social change by reviewing current literature and empirical data. The concept underscores the interdependent relationship of culture and transformation, focusing on the very importance of the subtleties of cultural assets to be understood and interventions made with their use to bring about beneficial development in society. This study may shed some light on the detailed relationship between culture and transition and offer essential information to administrators, practitioners, and researchers engaged in promoting just and lasting change.